ANALISIS STRUKTUR KLASTER INDUSTRI PADA SEKTOR PUBLIK - Jauhar Fikrinanda Rahmadi; Muhammad Yasin (CV. Denasya Smart Publisher, 2024)
National industrial strength is formed through interdependence, interconnectedness and mutual support between upstream, downstream, supporting and related industries. Thus, the manufacturing industry can reduce dependence on imports of capital goods, intermediate inputs, raw materials, components and spare parts. Industrial clusters, such as the leather industry in Sidoarjo, consist of subsystems providing raw materials and the leather tanning industry, as well as supporting industries that are intensively interconnected. Overseas industrial cluster policies function as an effective structural organization in increasing industrial competitive advantage through comparative advantage. In this way, industrial clusters can increase competitiveness and create national industrial strength.